How old is the Hebrew bible? a linguistic, textual, and historical study - Hendel, Ronald S. 1950-; Joosten, Jan 1959- (New Haven, CT Yale University Press, 2018)
From two expert scholars comes a comprehensive study of the dating of the Hebrew Bible The age of the Hebrew Bible is a topic that has sparked controversy and debate in recent years. The scarcity of clear evidence allows for the possibility of many views, though these are often clouded by theological and political biases. This impressive, broad-ranging book synthesizes recent linguistic, textual, and historical research to clarify the history of biblical literature, from its oldest texts and literary layers to its youngest. In clear, concise language, the authors provide a comprehensive overview that cuts across scholarly specialties to create a new standard for the historical study of the Bible. This much-needed work paves the path forward to dating the Hebrew Bible and understanding crucial aspects of its historical and contemporary significance
In English
Keywords: RELIGION / Biblical Studies / History & Culture